In Vitro and In Silico Studies of Soluble Epoxide Hydrolase Inhibitors from the Roots of Lycopus lucidus - Yoo Kyong Han; Ji Sun Lee; Seo Young Yang; Ki Yong Lee; Young Ho Kim (Plants, 2021)
Soluble epoxide hydrolase (sEH) is an enzyme that is considered a potential therapeutic target in human cardiovascular disease. Triterpenes (1–4) and phenylpropanoids (5–10) were isolated from Lycopus lucidus to obtain sEH inhibitors through various chromatographic purificationtechniques. The isolated compounds were evaluated for their inhibitory activity against sEH, and methyl rosmarinate (7), martynoside (8), dimethyl lithospermate (9) and 9″ methyl lithospermate (10) showed remarkable inhibitory activity, with the IC50 values ranging from 10.6 ± 3.2 to 35.7 ± 2.1 µM. Kinetic analysis of these compounds revealed that 7, 9 and 10 were competitive inhibitors bound to the active site, and 8 was the preferred mixed type inhibitor for allosteric sites. Additionally, molecular modeling has identified interacting catalytic residues and bindings between sEH and inhibitors. The results suggest that these compounds are potential candidates that can be used for further development in the prevention and treatment for cardiovascular risk.